Ca2+ transport in pancreatic beta-cells during glucose stimulation of insulin secretion. - Hellman, B; Gylfe, E; Berggren, P; Andersson, T; Abrahamsson, H; Rorsman, P; Betsholtz, C (Informa Healthcare, 1980)
The role of Ca2+ in the regulation of insulin secretion was evaluated using beta-cell-rich pancreatic islets isolated from ob/ob-mice. The glucose stimulation of the secretory activity is supposed to result from accumulation of Ca2+ in the submembrane cytoplasmic space. It is likely that this process reflects the balance between increased entry of Ca2+ into the beta-cells and an enhanced sequestration of Ca2+ in the organelle sinks. The proposed model can explain the cAMP potentiation of glucose-stimulated insulin release with suppression of the mitochondrial Ca2+ uptake. Furthermore, differences in the Ca2+ buffering capacity of the secretory granules may account for other characteristic features of glucose-stimulated insulin release, in particular its biphasic nature and sensitivity to suppression on withdrawal of nutrients.